2019
DOI: 10.1371/journal.pntd.0007050
|View full text |Cite
|
Sign up to set email alerts
|

Community based cross sectional study of podoconiosis and associated factors in Dano district, Central Ethiopia

Abstract: BackgroundPodoconiosis, affects lower limb, is an entirely preventable non-communicable tropical disease common in low income countries. Globally it is estimated that there are 4 million peoples with podoconiosis and nationally it is estimated that there are 1.56 million cases of podoconiosis. Even though nationwide mapping has been conducted including the current district under investigation, there are no studies conducted to identify factors associated with podoconiosis in the district. Hence, this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
17
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 22 publications
(27 reference statements)
9
17
2
Order By: Relevance
“…In the present study, of four stages of podoconiosis with characteristics of itchy swelling, shallow skin folds, and mossy lesion were identified by clinical nurses; stage II was the most common, followed by stage I, stage III, and stage IV, respectively. is agreed with nationwide study in Ethiopia [21,25] from Dano district, Central Ethiopia. e present study also shows that stage IV was absent in lower age and appeared at higher age (56-70) accompanied with secondary infection; furthermore, age groups and stages of lymphoedema have significant statistical association and agreed with an idea that incidence and severity of podoconiosis increase with age, likely due to cumulative exposure to irritant soil [24,26].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In the present study, of four stages of podoconiosis with characteristics of itchy swelling, shallow skin folds, and mossy lesion were identified by clinical nurses; stage II was the most common, followed by stage I, stage III, and stage IV, respectively. is agreed with nationwide study in Ethiopia [21,25] from Dano district, Central Ethiopia. e present study also shows that stage IV was absent in lower age and appeared at higher age (56-70) accompanied with secondary infection; furthermore, age groups and stages of lymphoedema have significant statistical association and agreed with an idea that incidence and severity of podoconiosis increase with age, likely due to cumulative exposure to irritant soil [24,26].…”
Section: Discussionsupporting
confidence: 72%
“…e present study identified that cases of podoconiosis were more in males than in females with male-to-female ratio of 1.9 : 1 which was in contrast to [23] in Wayu Tuka district, eastern Wollega, in which male-to-female ratio was 1 : 1.58 and 0.98 : 1 in Gojjam, Northern Ethiopia [22]. e risk difference could be due to occupationally (agricultural) linked trauma to the feet (poor habit of wearing shoes) and the cumulative effect of long-term exposure to the soil of the area during farming [24,25]. Present finding also unfolds that more than half cases of podoconiosis were found in age [18].…”
Section: Discussionmentioning
confidence: 95%
“…There was variability in reporting of female/male risks of developing podoconiosis. Some studies reported females are at greater risk of developing podoconiosis [ 24 , 27 ]; other indicated males were more affected [ 32 ]; still, others showed no sex differences [ 22 , 26 , 28 , 29 , 30 , 31 , 33 ]. Our systematic review revealed that being female increased the risk of developing podoconiosis.…”
Section: Discussionmentioning
confidence: 99%
“…A major and serious complication of podoconiosis is acute adenolymphangitis, which presents as a warm, painful sensation in the limbs, accompanied by fever 2. In addition to prolonged exposure to soil, many studies have shown that the prevalence of podoconiosis is associated with feet hygiene, shoe-wearing habit, gender, age, occupation, housing condition and income status 4–7…”
Section: Introductionmentioning
confidence: 99%
“…Podoconiosis is endemic in 345 districts of Ethiopia, the majority of cases being in Oromia, Southern Nations, Nationalities and Peoples’ and Amhara regional states 16. In Ethiopia, studies have shown that podoconiosis is significantly associated with soil texture and land topography,17 washing practices and frequency of shoe-wearing,4 18 family history, and being barefoot 5. Although simple and effective treatment strategies are available in Ethiopia, patients with podoconiosis tend to discontinue their treatment.…”
Section: Introductionmentioning
confidence: 99%